EVOLUSI BANK KONVENSIONAL DALAM PERSPEKTIF TEORI PUSH PULL MOORING - Pradila, Arfir; Teofilus, Teofilus (Prodi Magister Manajemen Universitas Wijaya Putra, 2024)
This study aims to identify differences in customer perceptions of push and pull factors in switching from conventional banking services to digital banking at Bank Mandiri Tanjung Perak Branch in Surabaya. The research methodology involves questionnaires for quantitative data collection and documentation to support the data. Analysis is conducted using the Push Pull Mooring (PPM) theory to evaluate the influence of Service Quality, Perceived Ease of Use, and Lifestyle on customers' Switching Intention. The findings indicate that for customers with less than 5 years of transaction experience, service quality and ease of use of digital services influence their intention to switch. For customers with more than 5 years of experience, service quality and ease of use have different impacts on switching intention. The t-test results show that switching intention is not significantly influenced by the duration of use (P value 0.93), but lifestyle significantly affects preference for digital services (P value 0.003). Perceived ease of use does not show a significant difference between the two groups (P value 0.716), while service quality shows a significant difference (P value 0.014). The application of these research findings to other Mandiri branches needs to consider demographics, strategy adaptation, and continuous evaluation. Bank Mandiri can optimize its services by focusing on customer retention, lifestyle, ease of user experience, and improving service quality. Understanding the interaction effects between these variables helps Bank Mandiri adapt holistic and customer-oriented strategies. Thus, Bank Mandiri can enhance its competitiveness in an increasingly dynamic market.